The impact of land-use and climate change on water and sediment yields in Batanghari Watershed, Sumatra, Indonesia - Ridwansyah, Iwan; Apip, Apip; Wibowo, Hendro; Rahmadya, Aldiano; Susiwidiyaliza, Susiwidiyaliza; Handoko, Unggul; Setiawan, Fajar; Utami, Nurya (Universiti Kebangsaan Malaysia, 2023)
The Batanghari River flows from the province of West Sumatra into the West Coast of Jambi, with the main river extending up to 870 km. Also, the Batanghari watershed Land use changes have shown a decreasing forest cover and an increasing agricultural area. Therefore, this study aims to calculate the impact of land use and climate change on water and sediment yield using Soil and Water Assessment Tools (SWAT) hydrological modeling. Land-use change analysis was performed with projections in 2040 while, near future and future climate projections under Representative Concentration Pathway (R.C.P.) 4.5 and 8.5 were used for global climate change scenarios. The results show a changing pattern of growing agricultural area and decreasing forest area in 1990, 1997, 2005, 2015, and 2040. SWAT hydrological model used for the simulation was calibrated automatically with SWAT-CUP and the results were validated on good criteria. The sensitivity analysis results showed that effective hydraulic conductivity in main channel alluvium (CH_K2) and Base flow alfa factor (Alfa_BF) formed the most sensitive parameters for discharge. Furthermore, the model simulation showed an increase in surface runoff and a decrease in lateral flow and base flow due to land-use changes, which increased sediment loading over time. The impact of climate change on water and sediment yield increased the average flow discharge ratio, resulting in more frequent droughts and floods events.